2013
DOI: 10.1021/jf401720q
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biological Activity of Antifungal Saponins from Shallot (Allium cepa L. Aggregatum Group)

Abstract: The n-butanol extract of shallot basal plates and roots showed antifungal activity against plant pathogenic fungi. The purified compounds from the extract were examined for antifungal activity to determine the predominant antifungal compounds in the extract. Two major antifungal compounds purified were determined to be alliospiroside A (ALA) and alliospiroside B. ALA had prominent antifungal activity against a wide range of fungi. The products of acid hydrolysis of ALA showed a reduced antifungal activity, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…The presence of all of these compounds with the exception of saponins and other metabolites like steroids and naphthoquinones has been reported in leaves of Diospyros species reviewed by Mallavadhani et al [7]. In addition, the antifungal activity of flavonoids, triterpenoids, and saponins against crop pathogens has recently been reported [39][40][41]. Using TLC (data not shown), we found that the sample collected during the rainy season had a higher intensity of flavonoid compounds.…”
Section: Resultssupporting
confidence: 51%
“…The presence of all of these compounds with the exception of saponins and other metabolites like steroids and naphthoquinones has been reported in leaves of Diospyros species reviewed by Mallavadhani et al [7]. In addition, the antifungal activity of flavonoids, triterpenoids, and saponins against crop pathogens has recently been reported [39][40][41]. Using TLC (data not shown), we found that the sample collected during the rainy season had a higher intensity of flavonoid compounds.…”
Section: Resultssupporting
confidence: 51%
“…3 acetylated triterpene saponins were also isolated from the roots of C. alba and C. lutea [30]. Saponins, terpenoids and polyphenolic compounds found in other plants were reported to possess immunomodulatory, anti-inflammatory, antioxidant, antiparasitic, antiviral, antispasmodic, antidiabetic, antifungal, antibacterial, antihyperglycemic and cytotoxic properties [12,[31][32][33][34][35][36][37][38]. The beneficial activity of C. lutea observed in this study might be due to these chemical constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal activity was found for saponins extracted from Allium cepa L. (Amaryllidaceae). The main saponins with the highest antifungal activity were alliospiroside A and alliospiroside B [38]. Further saponins with antifungal activity were extracted from leaves of Solanum chrysotrichum (Solanaceae), from berries of Phytolacca tetramera (Phytolaccaceae), or from fruits of Capiscum sp.…”
Section: Bammentioning
confidence: 99%